Status and ranking of factors affecting job motivation from the viewpoint of librarians of special libraries of Ahvaz city, Iran - Khademizadeh, Shahnaz (Revista Cubana de Información en Ciencias de la Salud, 2019)
The aim of this study was to investigate the status and ranking of job motivational factors using Herzberg Two-factor Theory. This is a descriptive-analytical survey, and researcher-made questionnaire was used for data collection with reliability of 0.92 based on Cronbach Alpha. The statistical population included librarians of 7 special libraries of Ahvaz city, Iran, out of which 53 responded to the questionnaire. Data analysis was done using SPSS and descriptive and statistical statistics. The results indicate that according to librarians' viewpoint, from hygiene or extrinsic factors of job motivation, three components of qualified supervisor, proper management of affairs and desirable working condition, and from intrinsic or subjective factors, three components of success, assignment of responsibilities, and sense of achievement are in the first to third ranks, respectively. On the other hand, appreciation and salary components are in the lowest ranks among other factors. Therefore, it can be concluded that the status of hygiene (extrinsic) factors and motivational (intrinsic) factors is satisfactory in the studied population. However, it is required to plan for improving the current condition and compensating weaknesses.